THE IMPORTANCE OF EFFECTIVE TECHNIQUES IN INCREASING VOCABULARY RANGE OF STUDENTS - Abdiyeva S. (Innovative Development in Educational Activities, 2023)
In the given article the development of new information and communication effects on teaching vocabulary are discussed, as proper understanding of professional competence and quality in communication are very important and up to date issue.